If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying z + -9 = 1 Reorder the terms: -9 + z = 1 Solving -9 + z = 1 Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '9' to each side of the equation. -9 + 9 + z = 1 + 9 Combine like terms: -9 + 9 = 0 0 + z = 1 + 9 z = 1 + 9 Combine like terms: 1 + 9 = 10 z = 10 Simplifying z = 10
| 6x-5=.5x-3 | | (v-7su^2)(v+su^2)=0 | | 3x+x+4=18+x | | -4-6y=21 | | 9sin^2x=4 | | 25=-6t^2+30t+1 | | 57=2(6)+2w | | 60-3n=n | | 12(6x+8)+3x=5x+25 | | 7+x-5=8 | | 88=5w+13 | | (b-2ya^2)(3b-3ya^2)=0 | | 3+5.3x=1 | | -6n-152=-26 | | 7h-4=24 | | 2x+4y^2-6y^2-9+1-x+3x= | | -4c+4-2x=-2(3x-2) | | 4(8x-7)-10(10-8x)+3(-3x+9)=-8(6-7x) | | (9x-31)+(7x-2)+(4x+33)=360 | | 48+(9x-3)=90 | | 2(x-6)-5=2(x-7)-3 | | 2*(10+9m)= | | 8(-6b-1)=-104 | | -6x+5y=25 | | -4x=24x+11 | | (a^2+3sv)(3a^2-sv)=0 | | 3(5x-7)-3(9-6x)+9(-8x+3)=-8(9-5x) | | 2x+6x-2=8x+10-15 | | 5(x+7)+3=5x+4 | | 8m-7=9m | | 3k+10=2k+21 | | 8x(2x-9)=-71 |